Differences in postural control between healthy and subjects with chronic ankle instability. (July 2022) - Esteves, José; Dinis, Ricardo; Fernandes, Orlando; Castro, Maria António; Oliveira, Raul; Pezarat-Correia, Pedro
Abstract: Introduction: Chronic ankle instability (CAI) is characterized by the occurrence of repetitive inversion mechanism of the ankle, resulting in numerous ankle sprains. CAI occurs in approximately 70% of patients with a history of a lateral ankle sprain. Many causes of functional ankle instability have been postulated and include deficits in proprioception, impaired neuromuscular-firing patterns, disturbed balance and postural control. Objective: The purpose of this study was to compare postural control behaviour in subjects with chronic ankle instability and healthy subjects, using the traditional linear and nonlinear variables for the centre of pressure (CoP) displacement, during one-leg stance on stable and unstable surfaces. Methods: 16 CAI subjects and 20 healthy subjects were evaluated with the single leg stance on a stable surface and an unstable surface, for 60 s with a force plate. The traditional linear variables like CoP displacement, CoP amplitude and CoP velocity were calculated. Variability of CoP displacement was also submitted to nonlinear analysis and the approximated entropy, sample entropy, correlation dimension and Lyapunov exponent were calculated. Results: On the stable surface, no differences between groups for all the traditional variables were found but the correlation dimension of CoP mediolateral displacement had lower values on the CAI group with statistical significance (p < 0.05). On the unstable surface, no differences were found neither with linear variable neither with variability nonlinear analysis. Conclusion: Correlated dimension of CoP displacement during one-leg stance on a stable surface was the only variable that show significant differences between the two groups. The lower values of this variable in the CAI subjects may implicate a balance control system with more difficulties to adapt to the environment and the task demands. More studies are needed to better understand CAI subjects balance control. Highlights: It is common to use posturography for the study of chronicle ankle instability (CAI). Traditional posturography didn't find differences between healthy and CAI subjects. Correlated dimension variable found differences between healthy and CAI subjects.